Light trapping for a‐Si:H/µc‐Si:H tandem solar cells using direct pulsed laser interference texturing. Issue 1 (27th November 2014) - Ring, Sven; Neubert, Sebastian; Schultz, Christof; Schmidt, Sebastian S.; Ruske, Florian; Stannowski, Bernd; Fink, Frank; Schlatmann, Rutger
<x xml:space="preserve">Abstract</x> We present a‐Si:H/µc‐Si:H tandem solar cells on laser textured ZnO:Al front contact layers. Direct pulsed laser interference patterning (DLIP) was used for writing arrays of one‐dimensional micro gratings of submicron period into ZnO:Al films. The laser texture provides good light trapping which is indicated by an increase in short‐circuit current density of 20% of the bottom cell limited device compared to cells on planar ZnO:Al. The open‐circuit voltage of the cells on laser textured ZnO:Al is almost the same as for cells on planar substrates, indicating excellent growth conditions for amorphous and microcrystalline silicon on the U‐shaped grating grooves. DLIP is a simple, single step and industrially applicable method for large area periodic texturing of ZnO:Al thin films. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)